ANALISIS PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Tri Yuwono; Mustabihatun Umriyah; Riswanto (JURNAL EKONOMI, 2019)
The company certainly has a goal of increasing company value and welfare for shareholders. The company's goals can be achieved by the company by paying attention to the capital structure and financial performance of the company value. This study aims to determine and analyze the effect of capital structure and financial performance on firm value. The data used in this study are secondary data from banking companies listed on the Indonesia Stock Exchange for the period 2015 - 2017 with a sample of 18 companies selected using purposive sampling. The data analysis method used is descriptive statistics and multiple linear regression analysis. The results of this study indicate that the capital structure has no effect on firm value. Financial performance has an effect on firm value. Simultaneously, capital structure and financial performance have an effect on firm value. Keywords: capital structure, financial permormance, firm value